Perlindungan Hukum Terhadap Korban Pedofilia Di Indonesia Dan Thailand - Rina Shahriyani Shahrullah; Devita Sari (Journal of Judicial Review, 2014)
Child is heir to a country that must be protected by all circles. Child protection is an activity to ensure and protect children and their rights in order to live, grow, develop and participate optimally in accordance with human dignity.This study used a normative legal research and data used are secondary data. Data collection techniques used in this research is secondary data and primary data as additional data. Data analysis method used is through qualitative analysis.Based on this research note that the legal protection of children in Indonesia and Thailand have referred to the Child Rights Convention of 1989. The legal protection of children in Indonesia set up more details about the sexual abuse of children than in Thailand. The effectiveness of child protection agencies in Thailand is more effective than the child protection agency in Indonesia.